Pharmaceuticals leaching from biosolids amended soils - von Hellens, Anastasia (SLU/Dept. of Aquatic Sciences and Assessment, 2015)
Biosolids are currently applied on arable land in order to recirculate nutrients from urban areas. Biosolids have been reported to contain organic con-taminants such as pharmaceuticals; thereby the impact of spreading of bio-solids on the environment has to be investigated. This study aims to investigate the transport of pharmaceuticals in lab-scale soil columns using undis-turbed soil of different texture (i.e. clay, loam and loamy sand). The selected pharmaceuticals included ß-blockers (i.e. atenolol, metoprolol, propranolol and sotalol), antidepressants (i.e. amitriptyline, carbamazepine, citalopram, diazepam, fluoxetine, lamotrigine, oxazepam, sertraline, venlafaxine and zolpidem) and antibiotics (i.e. azithromycin, ciprofloxacin, clarithromycin, norfloxacin, ofloxacin, roxithromycin, sulfamethoxazole and trimethoprim). The soil columns with the highest clay content showed highest leaching regarding both relative mass and concentration from 9 out of 12 selected pharmaceuticals. The leaching of the pharmaceuticals (absolute amount) decreased in order of clay > loam > loamy sand. Carbamazepine, metoprolol and oxazepam leached highest (absolute amount) whereas trimethoprim, fluoxetine and citalopram leached the lowest (absolute amount). This indicates that the soil texture affect the leaching behaviour of pharmaceuticals by rapid flow through macropores. A correlation between leaching behaviour and physicochemical properties of pharmaceuticals showed hydrophobicity to be significantly negatively correlated with leaching (p < 0.05, spearman correlation). However, the study also concludes that other properties (i.e. adsorption to organic carbon, half-life and water solubility) are important to investigate when assessing the transport of pharmaceuticals in undisturbed soils.